2016
DOI: 10.1007/s10661-016-5401-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of land suitability for urban development in Ahwaz County in southwestern Iran using fuzzy logic and analytic network process (ANP)

Abstract: The ever-increasing development of cities due to population growth and migration has led to unplanned constructions and great changes in urban spatial structure, especially the physical development of cities in unsuitable places, which requires conscious guidance and fundamental organization. It is therefore necessary to identify suitable sites for future development of cities and prevent urban sprawl as one of the main concerns of urban managers and planners. In this study, to determine the suitable sites for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 31 publications
0
30
0
1
Order By: Relevance
“…An analytical hierarchy process (AHP) and an analytical network process (ANP) are used to determine the weights for disaster potential for disaster-resistant communities on hillsides. e ANP, which is an extension of the AHP, adds feedback to the AHP to predict the internal relationships between all criteria, objectives, and projects using ratio scales, to allow robust decision-making processes [2,[17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…An analytical hierarchy process (AHP) and an analytical network process (ANP) are used to determine the weights for disaster potential for disaster-resistant communities on hillsides. e ANP, which is an extension of the AHP, adds feedback to the AHP to predict the internal relationships between all criteria, objectives, and projects using ratio scales, to allow robust decision-making processes [2,[17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…In various studies (Dong et al, 2008;Tudes and Yigiter, 2010;Kumar and Shaikh, 2012;Bagheri et al, 2013;Romano et al, 2015;Abebe and Megento, 2017;Ustaoglu and Aydinoglu, 2020), this has been con rmed. Studies have shown that current land use must be considered when choosing suitable sites for the development of urban green spaces and have identi ed the suitability of different land uses based on their use type (Uy, & Nakagoshi, 2008;Zhang et al 2013;Malmir et al 2016;Abebe and Megento 2017;Dagistanli, et.al. 2018).…”
Section: Ahp Weightsmentioning
confidence: 99%
“…The ANP is a multi-goal decision-making method that is used in economics, sociology, and management science to give decision makers a deep understanding of issues in specific situations where there are several evaluation factors to complicate the decision-making process [29][30][31][32]. The ANP involves five steps: (a) Forming the structure of the problem; (b) questionnaire design; (c) an eigenvector W and consistency test; (d) a test of the hierarchy consistency ratio; and (e) the use of a supermatrix and estimation of the weights of indicators.…”
Section: Analytic Network Processmentioning
confidence: 99%